Computer applications in environmental engineering : [proceeding] - International Conference on Computer Applications in Environmental Engineering (1998 : Selangor, Malaysia); Environmental Engineering Technical Division, IEM; Mara Institute of Technology (ITM) ([s.l] : [s.n], 1998)
06